#1**+1 **

Solve for x:

4 - (x)/(4) = 6

Put each term in 4 - (x)/(4) over the common denominator 4: 4 - (x)/(4) = 16/4 - (x)/4:

16/4 - x/4 = 6

16/4 - x/4 = (16 - x)/4:

(16 - x)/4 = 6

Multiply both sides of (16 - x)/4 = 6 by 4:

(4 (16 - x))/4 = 4×6

(4 (16 - x))/4 = 4/4×(16 - x) = 16 - x:

16 - x = 4×6

4×6 = 24:

16 - x = 24

Subtract 16 from both sides:

(16 - 16) - x = 24 - 16

16 - 16 = 0:

-x = 24 - 16

24 - 16 = 8:

-x = 8

Multiply both sides of -x = 8 by -1:

(-x)/(-1) = -8

(-1)/(-1) = 1:

**Answer: | x = -8**

Guest Jun 3, 2017